Micro-electrical Discharge Machining Processes Technologies and Applications - Kibria, Golam; Jahan, Muhammad P.; Bhattacharyya, B. (Materials Forming, Machining and Tribology,, 2019)
This book offers a comprehensive collection of micro electrical discharge machining (EDM) processes, including hybrid processes. It discusses the theory behind each process and their applications in various technological as well as biomedical domains, and also presents a brief background to various micro EDM processes, current research challenges, and detailed case studies of micro-manufacturing miniaturized parts. The book serves as a valuable guide for students and researchers interested in micro EDM and other related processes. .